Proceedings of the international conference industrial and civil construction 2021 - Klyuev, Sergey Vasil'yevich; Klyuev, Alexander Vasil'yevich (Springer, 2021)
This book gathers the latest advances, innovations, and applications in the field of construction design and management, as presented by researchers and engineers at the International Conference Industrial and Civil Construction 2021, held in Belgorod, Russia, on January 18-19, 2021. It covers highly diverse topics, including building materials, building constructions, structural mechanics and theory of structures, industrial and civil construction, environmental engineering and sustainability. The contributions, which were selected by means of a rigorous international peer-review process, highlight numerous exciting ideas that will spur novel research directions and foster multidisciplinary collaborations.